Demography of Transgender, Nonbinary and Gender Minority Populations - Baumle, Amanda K.; Nordmarken, Sonny (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book provides the first compilation of demographic research focused on transgender, nonbinary, and gender minority populations. It discusses the measurement and conceptualization challenges that shape demographic knowledge of these populations, including how we capture gender on surveys. It examines our current knowledge of demographic characteristics and health disparities and outcomes. Overall, this research demonstrates the increasing knowledge of gender variation at the population level. At the same time, it reveals the need for better survey questions, additional data, and inquiry into a broader subset of demographic questions for these populations as there is little understanding of fundamental demographic information, including migration or spatial distribution of transgender populations, fertility and household structure, labor market outcomes, or broader patterns of morbidity and mortality. The research set forth in this book lays the groundwork for a trans demography that would produce population-level knowledge of these populations and points researchers and policymakers toward needed areas of research, conceptualization, and data collection.
.Part 1: Conceptualization and Measurement -- Chapter 1. Barriers to a Comprehensive Demography of Transgender and Nonbinary Youth in the United States, Karnoski -- Chapter 2. Capturing Trans: Conceptualization, Measurement, and Shifts, Compton -- Chapter 3. Hidden (and not so hidden) messaging in top utilized U.S. social surveys: the persistence of heteronormative ideology and the gender binary, Tabler et. al -- Chapter 4. Gender as a Journey: Rethinking the Narratives around Identity Formation for Non-binary Individuals, Vega et. al -- Part 2: Population Characteristics and Public Attitudes -- Chapter 5. Trans mobility across borders: An intersectional account of trans diaspora in migration studies, Jorquera et. al -- Chapter 6.Demographic and Socioeconomic Analyses of the Transgender and Cisgender Populations, Poston et. al -- Chapter 7. Attitudes Toward Rights and Privileges for Transgender People: Evidence from a National Survey ExperimentDoan et. al -- Chapter 8.Work, Inequality, and the Transgender Population, Baumle -- Part 3: Health and Healthcare Disparities -- Chapter 9. Health and Healthcare Utilization among TGNC Black and Hispanic/Latinx Adolescents, Carter et. al -- Chapter 10. Protective and Restrictive Transgender-Specific U.S. State Policies and Mental and Physical Health Among Transgender and Other Gender Diverse People, Goldenberg and Stephenson -- Chapter 11. Transgender Health in the American South: Attitudes, Behaviors, Experiences, & Outcomes, Austin et. al -- Chapter 12. Correlates of Suicide Risk among Binary and Non-Binary Transgender Young Adults, Wilkinson et. al -- Conclusion: Current knowledge and future needed research.
Keywords: Demography; Population; Sex; Sociology; Population and Demography; Gender Studies; Sociology